A dual‐band branch line coupler for LTE 0.7 GHz and LTE 2.6 GHz frequencies. Issue 9 (22nd May 2019) - Zaidi, Aijaz M.; Beg, Mirza Tariq; Kanaujia, Binod K.; Kumar, Sachin; Srivastava, Kunal
Abstract: In this paper, a dual‐band branch line coupler (BLC) for Long Term Evolution (LTE) 0.7 GHz and LTE 2.6 GHz frequencies is designed and developed. A dual‐band quarter wave transmission line (DBQWTL) capable to perform dual band operation for frequency ratio >3 is also proposed. The dual band BLC is designed by replacing the quarter wave transmission line of the conventional single band BLC with the proposed DBQWTL. By means of even and odd mode analysis, the closed form design equations of the proposed DBQWTL are obtained. Considering the implementation viewpoint of the proposed BLC, the circuit parameter analysis is carried out. The proposed BLC performs dual band operation with maximum amplitude imbalance of 0.26 dB and phase deviation of 3.07°. It is found in the comparative analysis that the proposed BLC has novelty in terms of its operating frequency ratio range.